Clinical and Laboratory Characteristics and Outcome of Illness Caused by Tick-Borne Encephalitis Virus without Central Nervous System Involvement - Bogovič, Petra; Kastrin, Andrej; Lotrič-Furlan, Stanka; Ogrinc, Katarina; Županc, Tatjana Avšič; Korva, Miša; Knap, Nataša; Strle, Franc (Emerging infectious diseases, 2022)
Information on febrile illness caused by tick-borne encephalitis virus (TBEV) without central nervous system involvement is limited. We characterized 98 patients who had TBEV RNA in their blood but no central nervous system involvement at the time of evaluation. Median duration of illness was 7 days; 37 (38%) patients were hospitalized. The most frequent findings were malaise or fatigue (98%), fever (97%), headache (86%), and myalgias (54%); common laboratory findings were leukopenia (88%), thrombocytopenia (59%), and abnormal liver test results (63%). During the illness, blood leukocyte counts tended to improve, whereas thrombocytopenia and liver enzymes tended to deteriorate. At the time of positive PCR findings, 0/98 patients had serum IgG TBEV and 7 serum IgM TBEV; all patients later seroconverted. Viral RNA load was higher in patients with more severe illness but did not differ substantially in relation to several other factors. Illness progressed to tick-borne encephalitis in 84% of patients within 18 days after defervescence.